Tapping Into Creativity: Crafting Engaging Math Lessons for Middle Schoolers with Macromedia Flash - Sukamdi, Sukamdi; Lepik, Aira (Program Magister Teknologi Pendidikan Universitas Jambi, 2023)
The aim of the research is to design media based on Realistic Mathematics Education (RME) spatial material; producing RME media with Macromedia Flash for class IX educators and students building materials; knowing the responses of educators and students after using the media; find out the results of learning about curved sided space figures. RME media development refers to the model of William W. Lee and Diana L. Owens by going through four stages out of five existing stages, namely: analysis; product design; development; implementation; and evaluation. In this research, the evaluation stage was not carried out. The results of expert validation obtained an average score of 88.8%, individual trials an average of 81.33%, small group trials an average of 80.89%, educators' responses to the media an average of 87.33%, and responses students average 83.73%. The use of RME media in learning has an impact on learning outcomes, where the average learning outcome for the experimental class is 81.65 while the average learning outcome for the control class is 78.39. The differences in learning outcomes show that RME media is effective when used in classroom learning.Explore a dynamic approach to math education as students delve into real-world scenarios, navigating building spaces with interactive Macromedia Flash tools. This innovative learning media sparks curiosity and deepens understanding, fostering a practical grasp of mathematics concepts for middle school learners.